2018
DOI: 10.1111/blar.12742
|View full text |Cite
|
Sign up to set email alerts
|

Development, Citizenship, and Everyday Appropriations of Buen Vivir: Ecuadorian Engagement with the Changing Rhetoric of Improvement

Abstract: The Ecuadorian state frames its development interventions in infrastructure and human capital as advances in buen vivir or 'good living'. This paper reports ethnographic research that draws attention to everyday appropriations of state discourses on buen vivir in the Amazon and Andes. Non-state actors in marginalised communities often use state discourses strategically in engagements and negotiations with state actors. We argue that uses of official versions of buen vivir discourse often reflect such strategic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
1
0
2
Order By: Relevance
“…Esta falta de articulación ha derivado en una enorme confusión científica para definir que es el buen vivir socialista: Ramírez Gallegos (2010b) defiende que el socialismo del sumak kawsay tiene una identidad propia, De Sousa Santos (2010) que es una forma de socialismo del siglo XXI con ciertas particulares, Borón (2008) que socialismo del siglo XXI y del buen vivir son lo mismo, García-Linera (2015) que es un tipo de socialismo comunitario, Lyall et al (2018) que es una forma de apropiación estratégica, Pereira da Silva (2020) que es una estrategia socialista que ha vaciado de contenido al buen vivir, Vanhulst et al (2020) que es desarrollo ecomarxista, y Oviedo Freire (2016) que socialismo y sumak kawsay son dos conceptos totalmente incompatibles.…”
Section: Los "Buenos Vivires": Alternativas Al Desarrollo Y Desarroll...unclassified
See 1 more Smart Citation
“…Esta falta de articulación ha derivado en una enorme confusión científica para definir que es el buen vivir socialista: Ramírez Gallegos (2010b) defiende que el socialismo del sumak kawsay tiene una identidad propia, De Sousa Santos (2010) que es una forma de socialismo del siglo XXI con ciertas particulares, Borón (2008) que socialismo del siglo XXI y del buen vivir son lo mismo, García-Linera (2015) que es un tipo de socialismo comunitario, Lyall et al (2018) que es una forma de apropiación estratégica, Pereira da Silva (2020) que es una estrategia socialista que ha vaciado de contenido al buen vivir, Vanhulst et al (2020) que es desarrollo ecomarxista, y Oviedo Freire (2016) que socialismo y sumak kawsay son dos conceptos totalmente incompatibles.…”
Section: Los "Buenos Vivires": Alternativas Al Desarrollo Y Desarroll...unclassified
“…Por ello, algunos/as autores/as la denominan buen vivir estatista (Vanhulst et al 2020). No obstante, numerosos/as autores/as consideran que el buen vivir socialista no puede ser considerado parte del buen vivir, sino una forma de apropiación simbólica con fines políticos (Lyall et al 2018;Martínez Novo 2018).…”
Section: Introductionunclassified
“…After Gutiérrez deepened unpopular neoliberal reforms, Rafael Correa rose to power on a wave of popular opposition to austerity in Ecuador and Latin America, more broadly (Yates and Bakker 2014). Public sector investments in infrastructure, healthcare, welfare programmes and education ushered in a period of economic and political stability (Lyall, Colloredo-Mansfeld, and Rousseau 2018). As of August 20, 2018, the World Bank website indicated that, under the Correa regime, Ecuador had witnessed an average decline in GDP of 4.3 per cent and a 15-point decline in poverty from 37.6-22.5 per cent.…”
Section: Rural Governance In Modern Ecuadormentioning
confidence: 99%